MRI reveals scoliosis as a silent driver of lumbar facet joint degeneration in aging Ecuadorian adults - Pablo Cueva-Medina; Jorge Silva-Hidalgo; Fabricio González-Andrade (Scientific Reports)
Abstract Lumbar facet arthropathy (LFA) is a degenerative condition of the facet joints that contributes significantly to chronic low back pain (CLBP) yet remains underrecognized in standard diagnostic protocols. While aging and disc degeneration are established factors in the progression of LFA, the potential role of spinal deformities such as scoliosis has not been thoroughly investigated. This cross-sectional study examined the association between scoliosis severity and LFA in a non-surgical population of 284 Ecuadorian adults aged 30 to 80 years. Participants were classified by Cobb angle into normal, mild, moderate, and severe scoliosis categories and underwent MRI to assess facet joint degeneration at the L3–L4, L4–L5, and L5–S1 levels. Findings revealed that moderate scoliosis significantly increased the odds of severe LFA across all lumbar levels, particularly at L3–L4 (OR = 6.72) and L5–S1 (OR = 5.57). Mild scoliosis also posed a notable risk, with a threefold increase at L4–L5 and a twofold increase at L5–S1. Additionally, degeneration was more severe on the concave side of the scoliotic curve. Older age and female sex were also independently associated with more advanced degeneration. These results suggest that scoliosis, even in its mild forms, plays a significant role in the development and progression of LFA. The findings highlight the importance of including facet joint evaluation in routine scoliosis assessment and CLBP workups, particularly using MRI. Early identification of individuals at risk could inform preventive strategies and reduce long-term disability related to degenerative spinal disease.